2016
DOI: 10.1159/000444488
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and DNA Damage in Untreated First-Episode Psychosis in Adolescents

Abstract: Objective: Oxidative stress has been reported to play a role in the psychopathology of schizophrenia, though only a few studies have investigated the relationship between early-onset schizophrenia and oxidative stress. The aim of the present study is to evaluate the level of oxidative stress and the presence of DNA damage in first-episode psychosis (FEP) in adolescents. Methods: This study was conducted in the Department of Child Psychiatry of the Dicle University Hospital. It included 20 adolescent patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…Seven studies reported data on oxidative stress or inflammatory markers in EOP compared with healthy controls (Mico et al, 2011; Fraguas et al, 2012; Parellada et al, 2012; Martinez-Cengotitabengoa et al, 2014; Simsek et al, 2016b; Simsek et al, 2016a; Xu et al, 2016). Details of these 7 studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies reported data on oxidative stress or inflammatory markers in EOP compared with healthy controls (Mico et al, 2011; Fraguas et al, 2012; Parellada et al, 2012; Martinez-Cengotitabengoa et al, 2014; Simsek et al, 2016b; Simsek et al, 2016a; Xu et al, 2016). Details of these 7 studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the small numbers of studies included for each parameter, no meta-regression analyses could be performed. Separate meta-analyses based on 2 papers (Mico et al, 2011; Simsek et al, 2016b) providing specific data on GPx and cell/DNA oxidative damage in EOP patients with a follow-up diagnosis of schizophrenia as compared with controls did not yield significant results either (SMD=1.34 (95% CI: -1.08 to 3.76), P =.279 for GPx, and SMD=1.37 (95% CI:-1.43 to 4,18), P =.338 for cell/DNA oxidative damage). The quality of the included studies was in general low (supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations